Time Management Program and Its Effect on Work Stress among Head Nurses - Marwa Abd El Rahman Gaber; FatmaHamdy Hassan; Rabab Mahmoud Hassan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Effective time management has become increasingly important for head nurses to accomplishthe health care organizations’ objectives. Also, time management can help head nurses in balancing theirprofessional and personal lives . Learning how to manage nursing time at work will reduce work stress,burnout and gain control over work. Objective: the present study is conducted to evaluate the effect oftime management program for the head nurses on their work stress. Materials and Methods: A quasiexperimentalresearch design (intervention and control) with pretest and posttest has been conducted toachieve the aim of this study. The study was conducted at Ain-Shams University Hospitals. The subjects ofthe study included 115 head nurses working in Ain Shams University hospitals. The subjects were dividedinto two groups, intervention and control group. Results: The results indicated that there was a highlystatistical significant difference between pre /post, pre / follow up results regarding time managementknowledge level , time management skills , time wasters and work stress in favor of the intervention groupp-value <0.001, whereas there was no statistically significant difference or improvement in the controlgroup (p > .05). Conclusion: The study revealed that the head nurses work stress decreased markedly afterimplementing the time management program in the intervention group than the control group.